TINJAUAN KRIMINOLOGIS TERHADAP KEKERASAN DALAM RUMAH TANGGA YANG DILAKUKAN SUAMI TERHADAP ISTRI DI DESA TUNBAUN KECAMATAN AMARASI BARAT KABUPATEN KUPANG - Fallo, Erasmus Putra Suria; Fallo, Debi F. Ng; Djara Dima, Adrianus (Petitum Law Journal, 2023)
What factors cause domestic violence by husbands against wives in Tunbaun Village, West Amarasi District, Kupang Regency? What are the efforts to deal with cases of domestic violence by husbands against wives in Tunbaun Village, West Amarasi District, Kupang Regency? To find out the factors that cause perpetrators to commit domestic violence in Tunbaun Village, West Amarasi District, Kupang Regency. To find out efforts to deal with perpetrators who commit domestic violence in Tunbaun Village, West Amarasi District, Kupang Regency. Based on the results of research and discussion. As the researcher explained in CHAPTER III previously, it can be concluded: The factors that cause domestic violence are individual factors, economic partners and environmental factors. There are two factors that cause domestic violence, namely internal factors and external factors. Internal factors are factors that concern the personality of the perpetrator of domestic violence. Meanwhile, external factors are factors outside the perpetrator of domestic violence. Such as economic difficulties, infidelity, the environment and so on. Based on the conclusions above, the suggestions that researchers can give are as follows: So that the government carries out outreach to married couples who are prone to cases of domestic violence in each sub-district, either directly or indirectly, and so that each married couple understands religious teachings correctly. , and pay attention to each of their respective obligations.